What is a B chromosome? Early definitions revisited - Ferree, Patrick M.; Blagojević, Jelena; Houben, Andreas; Martins, Cesar [UNESP]; Trifonov, Vladimir A.; Vujošević, Mladen (Oxford University Press (OUP), 2024)
Since the discovery of B chromosomes, multiple different definitions of these selfish genetic elements have been put forth. We reconsidered early definitions in light of recently published studies. While there are many characteristics that vary among different B chromosomes, such as their evolutionary origins, size, segregation behaviors, gene content, and function, there is one defining trait of all B chromosomes: they are nonessential for the organism. The points raised here may be useful for framing future B chromosome studies and help guide the categorization of new chromosomal elements that are uncovered in genomic studies.
Keywords: B chromosomes; genetic drive; selfish genetic elements